Organizational culture and Knowledge Sharing Practices among Academic Staff in Library Schools in Southwest Nigeria - Osisanwo, Temitope A.; Ogunbanjo, Babatunde; Adeyeni, Mary T. (Communicate: Journal of Library and Information Science, 2025)
This study investigated the influence of organisational culture on knowledge sharing practices among academic staff in selected library schools in Southwest, Nigeria, using a descriptive survey design. A total of 84 academic staff were sampled across twelve institutions. The highest respondents were from the University of Ibadan and Federal University Oye-Ekiti (13.09% each). Findings revealed that organizational culture of academic staff is high, all respondents (100%) shared knowledge on innovative teaching techniques, while 96.4% shared conference opportunities, 95.2% shared career opportunities, and 94% shared information on highly rated journals. Innovative teaching techniques were the most frequently shared (????̄ = 3.57; SD = 0.5867), followed by research ideas (????̄ = 3.47; SD = 0.5906). Major knowledge-sharing channels included electronic discussions, departmental meetings, and face-to-face interactions (all 100%). Knowledge was shared primarily for educational (????̄ = 2.66; SD = 1.2547) and recreational (????̄ = 2.66; SD = 1.1336) purposes. A significant positive relationship was found between organizational culture and knowledge sharing (r = 0.408; p < 0.05), indicating that improved organizational culture enhances knowledge sharing. The study recommends institutional support for staff development, recognition, motivation, and policy-driven knowledge-sharing frameworks to promote teaching and research excellence.